Headline’s Meaning in On-Line Football Sport News - Gina Larasaty (Universitas Wiralodra, 2018)
The title of this study is Headline’s meaning in On-Line Football Sport News. The aims of this study are to describe the real meaning meaning contained in headline of on-line football sport news and to find out whether the meanings that appears in that headline and choice of words in the headline can represent the contents of the news, view from semantics study study. The data are taken and collected from headline of on-line football sport news from website Goal.com. In my study, the writer collected 20 data and analyzed it. The research method used in this study is descriptive method. The result shows that from 20 headlines, all of them can represent the content of the news and the words are used in the headline has conceptual and associative meaning that set in situational context. Based on the data, We can assume that headline always uses an unusual diction and has an implicit meaning to attract the attention of the reader. To attract the reader, Headline News use an unusual diction (figurative language, make it simple and direct). Then, based on this study, we can assume that from the headline we can know the contet or what the news is talking about.